Makassar City Community Perception of Mamminasata Bus Friends Service Promotion and Information on Social Media - Shahnyb, Nurafni; Mukti, Imam (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to analyze the perception of the people of Makassar City towards the promotion and information of Teman Bus Mamminasata services on social media. The method used in this study is a mixed-methods research approach with a sequential explanatory design. The results of the study indicate that although promotions on social media have succeeded in building positive initial awareness and interest, their effectiveness is hampered by the lack of transparency of information, especially regarding service changes such as corridor terminations. This causes negative sentiment, disappointment, and decreased public trust because information on social media is often considered inaccurate or out of date. The positive correlation between promotion and initial intention to use the service does not persist in actual usage decisions that are highly dependent on the reliability and availability of the service. Social media is recognized as a powerful tool for building brand awareness and providing basic information, but its effectiveness in building user trust and satisfaction is highly dependent on the consistency, accuracy, timeliness, and interactivity offered.